Turning Numbers into Knowledge : Mastering the Art of Problem Solving, Third Edition - Koomey, Jonathan G. (Analytics Press, 2017)
Intended for beginning analysts, students, and the people training them, this book bridges general business problem solving and mathematics for improved effectiveness in work and life. --